Breastfeeding Supports and Services in Rural Hawaii: Perspectives of Community Healthcare Workers - Jeanie L. Flood (Hindawi Limited, 2017)
Background. In the state of Hawaii, breastfeeding initiation rates are higher than the national average but fall below target rates for duration. Accessing breastfeeding support services is challenging for mothers living in rural areas of the state. Healthcare workers (HCWs) working with mothers and infants are in a key position to encourage and support breastfeeding efforts. The purpose of this study is to gain a better understanding of a Hawaiian community's (specifically Hilo, Hawai'i) breastfeeding service and support issues. Method. The qualitative study design utilized was a focused ethnography. This approach was used to gather data from participant HCWs (N=23) about their individual or shared experience(s) about the breastfeeding supports and services available in their community. An iterative process of coding and categorizing the data followed by conceptual abstraction into patterns was completed. Results. Three patterns emerged from the qualitative interviews: Operating within Constraints of the Particular Environment, Coexisting Messages, and Process Interrupted. Participants identified a number of gaps in breastfeeding services available to their clients including the lack of available lactation consultants and the inconsistent communication between hospital and community providers. A number of implications for practice and further research were suggested within the results and are discussed.